A practical approach to ichthyoses with systemic manifestations. Issue 6 (22nd August 2016) - Saral, S.; Vural, A.; Wollenberg, A.; Ruzicka, T.
Abstract : Inherited ichthyoses are rare disorders in terms of patient numbers, but abundant in terms of clinical‐genetic subtypes. These disorders are often associated with severe systemic manifestations, in addition to significant medical, cosmetic and social problems. There are 17 subtypes of syndromic ichthyosis identified so far and most patients with these syndromes are living in countries with high consanguinity rates. Frequently, clinicians cannot make a definitive diagnosis and patients are not managed properly owing to the rarity and complexity of these disorders. These difficulties make this group of ichthyosis and the patients living with them 'orphan'. After skin and skin appendages, nervous system is the most frequently involved system in ichthyosis syndromes. Thus, association of ichthyosis with neurological symptoms provides an important clue for diagnosis. In this article, we aim to increase clinicians' comprehension of ichthyosis syndromes by providing a symptomatology‐based approach based on this observation. Additionally, we provide a review of ichthyosis syndromes, with special emphasis on neurological symptoms, hoping to attract interest to this complicated field. Abstract :